2020
DOI: 10.3389/fnmol.2020.00016
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Induces Apoptosis of PC12 Cells Through LPA1 Receptor/LPA2 Receptor/MAPK Signaling Pathway

Abstract: Lysophosphatidic acid is a small extracellular signaling molecule, which is elevated in pathological conditions such as ischemic stroke and traumatic brain injury (TBI). LPA regulates the survival of neurons in various diseases. However, the molecular mechanisms underlying LPA-induced neuronal death remain unclear. Here we report that LPA activates LPA1 and LPA2 receptors, and the downstream MAPK pathway to induce the apoptosis of PC12 cells through mitochondrial dysfunction. LPA elicits the activation of ERK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…MAPK pathways, such as ERK1/2, p38, and c-Jun N-terminal kinase (JNK), are known to participate in NLRP3 inflammasome by upregulating NLRP3 [ 29 , 30 , 31 ]. These pathways are effector ones of LPA 1 [ 32 ]. Therefore, the LPA/LPA 1 signaling axis might regulate NLRP3 upregulation by activating MAPKs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK pathways, such as ERK1/2, p38, and c-Jun N-terminal kinase (JNK), are known to participate in NLRP3 inflammasome by upregulating NLRP3 [ 29 , 30 , 31 ]. These pathways are effector ones of LPA 1 [ 32 ]. Therefore, the LPA/LPA 1 signaling axis might regulate NLRP3 upregulation by activating MAPKs.…”
Section: Resultsmentioning
confidence: 99%
“…All these signaling pathways can influence NLRP3 inflammasome activation as players for the priming signal to induce NLRP3 upregulation [ 26 , 27 , 29 , 30 , 31 ]. They are also well-known as effector pathways after LPA 1 activation [ 32 ]. Indeed, the current in vitro study clearly showed that suppressing LPA 1 activity by AM152 treatment attenuated the activation of NF-κB, ERK1/2, and p38 in LPS-primed BMDMs following LPA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that baicalein could activate PI3K/AKT pathway, inhibit caspase activation and reduce cerebral infarct volume in MCAO rats [66]. Besides, formononetin mediated neuroprotection against cerebral ischemia/reperfusion in rats via downregulation of the Bax/Bcl-2 ratio and upregulation PI3K/Akt signaling pathway [67]. MAPK signaling pathways may be a therapeutic targets for stroke [68].…”
Section: Discussionmentioning
confidence: 98%
“…Besides, formononetin mediated neuroprotection against cerebral ischemia/reperfusion in rats via downregulation of the Bax/Bcl-2 ratio and upregulation PI3K/Akt signaling pathway [ 66 ]. The MAPK signaling pathway may be a therapeutic pathway for stroke [ 67 ]. Researches showed that suppressing the NF- κ B and MAPK signaling pathways would downregulate the expression of proinflammatory factors.…”
Section: Discussionmentioning
confidence: 99%